Multiplication of early generation planting materials and demonstration of vegetatively propagated crops for mixed farming system in North Shoa, Ethiopia - Girma, Natnael; Geto, Getaneh; Ayele, Alemayehu; Firew, Tigist; Assefa, Shanbel; Managido, Demis; Kassa, Yehuala; Mamo, Dejenie; Kemal, Seid Ahmed; Bishaw, Zewdie (International Center for Agricultural Research in the Dry Areas, 2023)
The highlands of North Shoa in Amhara region are dominated by cereals (wheat, barley and tef) followed by food legumes. The productivity of cereals and food legumes is low due to biotic and abiotic factors as well as insufficient input supplies like planting materials and other inputs. Farmers are trying to include vegetatively propagated horticultural crops (tubers, bulbs, and fruit trees) into the farming systems. Horticultural crops are very important to diversify diets, incomes and reduce risks of cereal and legume crop production. There are many temperate fruits (apple, peach, pear, plum etc), potato and garlic varieties developed by the agricultural research system but most of them are not demonstrated to the farming communities. Horticultural crops are becoming important due to increased small scale irrigation in the highlands as well as promotion and awareness programs on nutrition.